TEKNOLOGI AI DALAM MEMPERKAYA INTERPRETASI DAN PEMAHAMAN FIQH SEBAGAI REVOLUSI METODOLOGI - Faza, Amrar Mahfuzh (Program Studi Hukum Keluarga Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
The digital revolution in Islamic studies, especially Fiqh, marks a new era in understanding and interpreting Islamic law through Artificial Intelligence (AI) technology. In Islamic Family Law, the challenges of interpreting and applying law in a dynamic socio-cultural context require innovative research methodologies. This study fills the knowledge gap by integrating AI into Fiqh methodology, providing a new perspective in addressing contemporary issues in Islamic Family Law. Using qualitative and descriptive-analytical approaches, this study combines analysis of Islamic legal norms with empirical observations of AI applications, analyzing data from journal reviews, documentation, and literature. The results show that AI can identify patterns and themes in relevant Islamic legal texts, facilitating more dynamic and evidence-based interpretations, and paving the way for a broader understanding of legal principles in the context of modern life. The implications for theory and practice in Islamic Family Law are significant, encouraging integration between Islamic legal tradition and technological innovation, and offering more adaptive solutions to evolving issues in Islamic Family Law. This study suggests the development of AI algorithms that are more sensitive to socio-cultural contexts and expanding the database for analysis as future research directions.